Practical Japanese conversation (The association for overseas technical scholarship, 1976)
This books consists of thirty lessons. Each lesson is organized in the following way: basic patterns of expression to be mastered in the lesson, grammar explanation, drill, vocabulary, daily expressions, maily greetings or idiomatic expressions.